Analysis of vadose zone inhomogeneity toward distinguishing recharge rates: Solving the nonlinear interface problem with Newton method. Issue 11 (18th November 2016) - Steward, David R.
Abstract: Recharge from surface to groundwater is an important component of the hydrological cycle, yet its rate is difficult to quantify. Percolation through two‐dimensional circular inhomogeneities in the vadose zone is studied where one soil type is embedded within a uniform background, and nonlinear interface conditions in the quasilinear formulation are solved using Newton's method with the Analytic Element Method. This numerical laboratory identifies detectable variations in pathline and pressure head distributions that manifest due to a shift in recharge rate through in a heterogeneous media. Pathlines either diverge about or converge through coarser and finer grained materials with inverse patterns forming across lower and upper elevations; however, pathline geometry is not significantly altered by recharge. Analysis of pressure head in lower regions near groundwater identifies a new phenomenon: its distribution is not significantly impacted by an inhomogeneity soil type, nor by its placement nor by recharge rate. Another revelation is that pressure head for coarser grained inhomogeneities in upper regions is completely controlled by geometry and conductivity contrasts; a shift in recharge generates a difference Δ p that becomes an additive constant with the same value throughout this region. In contrast, shifts in recharge for finer grained inhomogeneities reveal patterns with abrupt variations across their interfaces. Consequently, measurements aimed at detecting shifts in recharge in a heterogeneous vadose zone by deciphering the corresponding patterns of change in pressure head should focus on finer grained inclusions well above a groundwater table. Abstract : Nonlinear interface conditions in the quasilinear formulation are solved for inhomogeneities in the vadose zone Patterns in pressure head distribution and pathline geometry are analyzed across variations in recharge rate A shift in recharge rate becomes evident by changes in pressure around finer grained inhomogeneities well above groundwater